2021
DOI: 10.1038/s42003-021-02029-w
|View full text |Cite
|
Sign up to set email alerts
|

Structure and function analysis of a potent human neutralizing antibody CA521FALA against SARS-CoV-2

Abstract: Severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is the causative agent of the ongoing COVID-19 pandemic, which has resulted in more than two million deaths at 2021 February . There is currently no approved therapeutics for treating COVID-19. The SARS-CoV-2 Spike protein is considered a key therapeutic target by many researchers. Here we describe the identification of several monoclonal antibodies that target SARS-CoV-2 Spike protein. One human antibody, CA521FALA, demonstrated neutralization poten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 37 publications
0
11
0
Order By: Relevance
“…In this study, the safety of a single-dose injection of LY-CovMab was as expected for a full-length recombinant human antibody in all five dose groups from 30 to 2400 mg [ 5 ]. We did not observe injection site reactions and hypersensitivity reactions, which have been reported in studies of other neutralizing antibodies [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 91%
See 4 more Smart Citations
“…In this study, the safety of a single-dose injection of LY-CovMab was as expected for a full-length recombinant human antibody in all five dose groups from 30 to 2400 mg [ 5 ]. We did not observe injection site reactions and hypersensitivity reactions, which have been reported in studies of other neutralizing antibodies [ 6 , 7 ].…”
Section: Discussionmentioning
confidence: 91%
“…Preclinically reported data from LY-CovMab effectively inhibiting pseudovirus and authentic virus infection in vitro and in vivo by interfering with the mechanism that the virus attaches to the host cell suggested that it could be a promising SARS-CoV-2 neutralizing antibody candidate [ 5 ]. Consistent with our preclinical finding, LY-CovMab displayed a good safety and pharmacokinetic profile in the first-in-human study, which supported its clinical potential.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations